The use of glasses for refractive disorder: a study from the perspective of an eye health. - Raimah; Mat, Bakri; Arbak, Salwani (Archivos Venezolanos de Farmacología y Terapéutica, 2022)
Currently, 2.2 billion people worldwide are experiencing vision impairment. At least 1 billion of them can be prevented by wearing proper glasses. Ironically, is it being difficult to distinguish between those who wear glasses due to refractive disorders and those who wear glasses to look fashionably trendy. This study aims to identify the behavior of eyewear users from the perspective of eye health based on sources from journals published in 2010-2020. The research methodology used is a systematic literature review by analyzing available literature relevant to the issue under study. Preliminary results show that the prevalence of refractive disorders is high and awareness of eye health needs is still low. There is a different attitude toward wearing glass between urban and rural consumers. Eye care services as a health system are needed to provide services and the importance of the proper use of glass as an aid for better vision and reduce the burden to vision due to refraction errors.